2018
DOI: 10.1039/c8cc02822b
|View full text |Cite
|
Sign up to set email alerts
|

Two transition metal phosphonate photocatalysts for H2 evolution and CO2 reduction

Abstract: Two transition metal (Co and Ni) ion phosphonates as isostructural organic inorganic hybrids are prepared and investigated in terms of photocatalytic hydrogen evolution from water and CO2 reduction under UV light irradiation. A photocatalytic mechanism of ligand-to-metal charge transfer (LMCT) is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The 2 + oxidation state of nickel in NiWPPA-4 was confirmed by the spin energy gap (18 eV) between Ni2p 3/2 and 2p 1/2 . [41] Figure 3c illustrates the high resolution spectra with binding energies at 34 and 36 eV, which could be assigned to the octahedral tungsten(VI) 4f 7/2 and 4f 5/2 spectra, respectievely. [42] Figure 3d shows the high resolution O 1s spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 + oxidation state of nickel in NiWPPA-4 was confirmed by the spin energy gap (18 eV) between Ni2p 3/2 and 2p 1/2 . [41] Figure 3c illustrates the high resolution spectra with binding energies at 34 and 36 eV, which could be assigned to the octahedral tungsten(VI) 4f 7/2 and 4f 5/2 spectra, respectievely. [42] Figure 3d shows the high resolution O 1s spectra.…”
Section: Resultsmentioning
confidence: 99%
“…[33] The strategy highlighted here is ligand extension through linking some non-pillaring "spacer" groups to the skeleton of the layered metal phosphonates, facilitating the production of pore structure, and adjustment of the pore environment, which greatly promotes the early scientific research of porous metal phosphonates. Also, the physicochemical properties of porous metal phosphonates through ligand extension strategy are summarized in Table 1, [34][35][36][37][38][39][40][41][42][43][44] which implies the applicability of this strategy for pore generation. However, it is noted that the substitution in this route is random, leading to narrow pore size distribution.…”
Section: Linking Non-pillaring "Spacer" Groupsmentioning
confidence: 99%
“…Very recently, Huang et al reported the bimetal Co-Ni phosphonates as photocatalysts for hydrogen evolution from water and CO 2 reduction under UV light irradiation. [44] It was revealed that Ni + or Co + generated under light irradiation functioned as the active site to efficiently reduce proton in water or CO 2 . [44] This work highlighted the great potential of metal phosphonates for photocatalysis due to the versatile coordination chemistry of metal active sites and organic ligands.…”
Section: Metal Complexes As Catalytic Sitesmentioning
confidence: 99%
“…Metal phosphonates hold great potential in the fields of catalysis and energy due to their combination of the specificity of organic groups and inorganic species. [49][50][51] The simple calcination of metal phosphonates is an efficient way to prepare metal phosphates, during which the graphitic carbons can be in-situ produced and coated on metal phosphate particles. The generated graphitic carbon layer can endow the catalyst with good stability and conductivity.…”
Section: Organophosphonate-derived Strategymentioning
confidence: 99%
“…The diversity of coordination chemistry of metal phosphates leads to various local coordination environment around the center of metal ions. Metal phosphonates hold great potential in the fields of catalysis and energy due to their combination of the specificity of organic groups and inorganic species . The simple calcination of metal phosphonates is an efficient way to prepare metal phosphates, during which the graphitic carbons can be in‐situ produced and coated on metal phosphate particles.…”
Section: Synthesis Strategies Of Transition Metal Phosphatesmentioning
confidence: 99%